Investigando as concepções dos estudantes do ensino fundamental ao superior sobre ácidos e bases - Figueira, Angela Carine Moura (2010)
This research aims at diagnosing alternative conceptions to scientific knowledge of students in Elementary Education, Middle and Upper on acids and bases. The survey was conducted between 2008 and 2009 and applied to 26 primary school students (ninth year), 36 high school (third year) and 51 Degree in Chemistry (26 freshmen and 25 trainees) totaling 113 students. The instrument used for data collection was mainly made up of open questions where the students described their concepts of acids and bases. The overall results of this study showed that students, after receiving formal instruction on acids and bases continue to use simplistic views on the subject many times in this work, we found misconceptions even among senior college students in the Degree Course in Chemistry. We realize that in general, the Arrhenius model prevails among the students, however, can not be said if students really understand acids and bases as particles or if they perceive these substances as mere words. Confusion between the various theories acid base were very common here, which leads us to believe that the teaching content too complex for the primary and secondary education become conflicting for the student, which does not contribute to an appropriation of such knowledge. In short, we can infer that this inventory of alternative conceptions expressed by students for the contents acids and bases is necessary because the importance of these concepts disclosed and discussed primarily with science teachers. Therefore, we expect to support a significant learning effectively through reflection on students' previous conceptions, which are an important tool for the proposition didactic classroom, since the strong resistance to a conceptual change that students present.